2021
DOI: 10.1155/2021/9913468
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Cultural Tourism Passenger Flow Prediction Model in the Yangtze River Delta Based on Regression Analysis

Abstract: Cultural tourism has gained much attention in the last decade and has promoted the preservation of a variety of tangible and intangible assets of culture. In order to accurately predict the cultural tourism passenger flow in the Yangtze River Delta and improve its economic benefits, this paper designs the prediction model of cultural tourism passenger flow in the Yangtze River Delta based on regression analysis. Taking the competitiveness of passenger flow as the core, this paper selects 28 indexes from four a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In this study, a cultural tourism passenger ow forecast framework is designed by taking into account a wide range of in uences. Experimentation has shown that this model can effectively estimate passenger ow in a real application, resulting in a large rise in the quantity of cultural tourist revenue [15]. Via geo-referenced data, they looked at the distribution of user check-ins across ten unique Shanghai neighborhoods.…”
Section: Related Workmentioning
confidence: 99%
“…In this study, a cultural tourism passenger ow forecast framework is designed by taking into account a wide range of in uences. Experimentation has shown that this model can effectively estimate passenger ow in a real application, resulting in a large rise in the quantity of cultural tourist revenue [15]. Via geo-referenced data, they looked at the distribution of user check-ins across ten unique Shanghai neighborhoods.…”
Section: Related Workmentioning
confidence: 99%
“…Although the GA-CNN-LSTM algorithm has higher accuracy in peak hours than other algorithms, the overall prediction accuracy for peak hours is still insufficient. Xu [12] designed a regression-analysis-based model for predicting cultural tourism flows in the Yangtze River Delta, with the competitiveness of flows as the core, and selected 28 indicators from four aspects: cultural tourism brand resources, cultural tourism support and protection, and urban tourism market income, to build an evaluation index system for the influencing factors of flows, and the designed model has a promising fit. Chen et al [13] combined residual networks with fully connected networks to provide an enhanced Quad-ResNet model for predicting the regional tourist flow of rural tourism.…”
Section: Introductionmentioning
confidence: 99%